Evaluation of Drug Planning and Procurement Using the ABC-VEN and Reorder Point (ROP) Methods at Belik Public Health Center, Pemalang Regency In 2023 - Iva Rinia Dewi; Annas Arfianto; Feri Kanti Rahayu; Arinda Nur Cahyani (International Journal of Public Health, 2024)
Community Health Centers (Puskesmas) are facilities established to implement promotive, preventive, curative, and rehabilitative health services by the government, local authorities, and the community. The system of drug planning and procurement plays a pivotal role in determining drug availability and the budget allocation required. This study aims to evaluate the process of drug planning and procurement using a combination of the ABC-VEN and Reorder Point (ROP) methods at the Belik Community Health Center, Pemalang Regency. This research is a descriptive analysis employing a retrospective case study design with data collection from January to December 2023 and supported by interviews. The results show that the ABC-VEN combination analysis identified: AV group (1 item; 0.29%; cost IDR 4,662,000), AE (45 items; 12.86%; IDR 271,578,813), AN (7 items; 2.00%; IDR 65,272,502), BV (7 items; 2.00%; IDR 7,825,526), BE (53 items; 15.14%; IDR 70,352,382), BN (11 items; 3.14%; IDR 15,283,936), CV (19 items; 5.43%; IDR 3,687,488), CE (194 items; 55.43%; IDR 42,690,036), and CN (13 items; 3.71%; IDR 2,779,589). Drugs in groups AN, BN, and CN (Additional group) should be prioritized for reduction; AE, BE, and CE (Main group) are second priority; while AV, BV, and CV (Priority group) must always be available. The highest Reorder Point (ROP) was for Dexamethasone at 64,067 tablets, while the lowest was Betason skin ointment with 0 tubes.